Bilingüismo en Santiago de Cali: Análisis de la evolución de los resultados de las Pruebas SABER 11 (2017)
In the following installment of Bilingualism in Santiago de Cali: Analysis of the evolution of the results of the Saber 11 Tests, the results of the public-private education system in the subject and the process it has been going through are presented in an analytical and comparative perspective. the country from some of its capital cities (Barranquilla, Bogotá, Medellín, Bucaramanga and Cali) in order to open its borders and gradually and at all levels insert itself into that 74% of global communications in English, from business, academia, travel, cultural exchanges, cinema, literature, art and the economy. From the Ministry of Education, in particular, the challenge was raised in 2010 to work for 4 years with strategies defined in the Program to Strengthen the Development of Competencies in Foreign Languages (PFDCLE) to achieve that by 2014 40% of 11th-grade students in the country graduated with a B1 level of English. Despite the efforts of the MEN to implement training, endowment, immersion and awareness-raising strategies, framed in the aforementioned Program, significant progress has not been made in achieving this goal. In contrast, today there is a clear need to begin to massify English as a window of opportunity that facilitates, on the one hand, access to qualified jobs in key sectors for the development of the country such as tourism, BPO and health and, on the other hand, it dynamizes the economy and strengthens the capacities of regions such as the Valle del Cauca to be a pole of attraction for foreign investment and to open access to the market of the American Pacific and Asia. In the graphs and analyzes below it is possible to evidence, in recent years, some first movements in the results of the official sector in order to begin to close the gap with the private sector. In Cali, for the first time, there is an official B1 school, with 122 students who took the Saber 11 test. But if we analyze it in perspective with other capital cities, we find that Medellín and Bucaramanga each have one school at the B1 level, with 41 and 87 students evaluated, respectively. Barranquilla has two schools at B1 (92 students) and Bogotá, three schools (317 students). The gap remains wide and the challenge is great for everyone. From 2008 to 2013, the percentage of high school graduates at B1 level or higher has gone from 5 to 6%, well below the 40% target, which suggests that the challenge of generating in-depth transformations not only covers official schools but also non-bilingual private schools, particularly those focused on socioeconomic levels 1, 2 and 3. If Cali manages to do things right in terms of qualification of bilingual human talent in English, by 2026 there would be approximately 157 large foreign investment projects landing and developing in a sustained manner, according to projections from Invest Pacific. Doing things right, as highlighted in this edition, implies working on crucial issues such as raising the learning of English to a priority for both decision-makers and families; moving from the conviction of the importance of knowing English to concrete and forceful actions, with actions focused on the need and addressing the learning context; and that these actions add up so that English obtains at the regional and national level a meaning and / or social value that prevails in everyone's needs. In Chile, they have been working since 2003 with English Opens Doors as a Government program to which they have invested enormous efforts to achieve structural transformations from social valuation itself. By 2014, they managed to close the gap in the lack of teachers licensed in pedagogy for the teaching of English and focused their policy on ensuring that students and teachers spoke English as a unique opportunity to open their borders. In addition, as a relevant element of dignifying the role of English teachers, they have been classified as the new Alchemists of Education. In Cali, in particular, there is a positive alignment of forces from different sectors, all convinced and in the task of convincing an important substrate of the population in order to guide joint efforts that allow raising the learning of English to a socioeconomic and regional development priority. The path, like the goal set for 2014, is a long one to travel, but inevitably important, urgent and necessary.